Existence of solutions of nth order impulsive integro-differential equations in Banach spaces - Shihuang Hong; Zeyong Qiu (Electronic Journal of Qualitative Theory of Differential Equations, 2008)
In this paper, we prove the existence of solutions of initial value problems for nth order nonlinear impulsive integro-differential equations of mixed type on an infinite interval with an infinite number of impulsive times in Banach spaces. Our results are obtained by introducing a suitable measure of noncompactness.